EVALUASI DISTRIBUSI LOGISTIK OLEH KOMISI PEMILIHAN UMUM KABUPATEN YALIMO PADA PEMILIHAN UMUM TAHUN 2019 DI KABUPATEN YALIMO - Mita Yulia; Nur Aedah; Renida J. Toroby (Universitas Cenderawasih, 2023)
This research aims to evaluate the distribution of logistics in the 2019 elections in Yalimo Regency. Then describe what factors support and hinder the 2019 election logistics distribution process in Yalimo Regency. As well as formulating what efforts need to be made to improve the quality of election logistics distribution in the Yalimo District. This research uses descriptive qualitative research. Determination of key informants was carried out purposively by selecting representatives from the Yalimo Regency KPU, Yalimo Regency Bawaslu, TNI/Polri Security Officers, and the PPS Committee. Data collection techniques used were in-depth interviews and observation. Data analysis includes the stages of data reduction, data presentation, and conclusion. The results of the study show that the evaluation of the distribution of logistics for the 2019 election in Yalimo District has been quite effective; in terms of efficiency it is still less efficient; and in terms of responsiveness, the implementation of election logistics distribution to organizers is very responsive. The supporting factors are the participation of relevant stakeholders, the existence of technical regulations as guidelines, and the existence of an operational budget. The inhibiting factors are geographical and topographical conditions which are a challenge in itself, because it is difficult to reach, coupled with inadequate KPU personnel. Efforts made to improve the quality of election logistics distribution are by increasing funding, the planning process at an early stage needs to be considered to anticipate delivery delays, and improving communication and coordination to establish collaboration between agencies in implementing policies.